2018
DOI: 10.1177/0003489418803969
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Motor-Evoked Potential Monitoring on Facial Nerve Outcomes after Vestibular Schwannoma Resection

Abstract: Objectives: Assess the utility of intraoperative transcranial facial motor-evoked potential (FMEP) monitoring in predicting and improving facial function after vestibular schwannoma (VS) resection. Study Design: Retrospective chart review. Methods: Data were obtained from 82 consecutive VS resections meeting inclusion criteria. Sixty-two cases were performed without FMEP and 20 with FMEP. Degradation of FMEP response was defined as a final-to-baseline amplitude ratio of 0.5 or less. House-Brackmann (HB) grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Sensitivity and negative predictive values were found to be higher than those reported recently by Tawfik et al 19 This observation can be explained by the fact that a single alarm criterion was applied across different lesion types. This criterion The numbers of true positive (TP; permanent MEP decrease above that threshold at the end of resection and new deficits), true negative (TN; MEP decrease under that threshold at the end of resection and no deficit), and false negative (FN; MEP decrease under that threshold at the end of resection but new deficits) are indicated with sensitivity (TP/(TP þ FN)) and with negative predictive value (TN/(TN þ FN)).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Sensitivity and negative predictive values were found to be higher than those reported recently by Tawfik et al 19 This observation can be explained by the fact that a single alarm criterion was applied across different lesion types. This criterion The numbers of true positive (TP; permanent MEP decrease above that threshold at the end of resection and new deficits), true negative (TN; MEP decrease under that threshold at the end of resection and no deficit), and false negative (FN; MEP decrease under that threshold at the end of resection but new deficits) are indicated with sensitivity (TP/(TP þ FN)) and with negative predictive value (TN/(TN þ FN)).…”
Section: Discussioncontrasting
confidence: 75%
“…This alarm criterion could have led to a lower sensitivity, with FN cases, and could have contributed to the conclusion that neuromonitoring did not decrease the rate of facial nerve deterioration. 19 Seidel et al 16 reported a low complication rate using continuous direct electrical stimulation during the resection of vestibular schwannomas. In the present series, direct electrical stimulation was usually performed temporarily and was not always done before the observation of MEP decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Function preservation of surrounding structures and mainly the 7 th nerve is an important part of VS surgery. The surgical outcome in sporadic VS is associated with the following factors: tumor size, adhesion to the brainstem and CNs, the use of CN monitoring technology and surgeon's experience [64][65][66][67][68][69]. Surgical treatments include subtotal resection (STR), near-total resection (NTR) and total resection [70].…”
Section: Sporadic Vsmentioning
confidence: 99%
“…The introduction of intraoperative facial electromyographic (EMG) recordings has allowed the surgeon to monitor FN function during surgery and better accomplish an atraumatic dissection. A robust FN response to direct stimulation has been associated with excellent postoperative FN function, although precise metrics have yet to be defined and this phenomenon is sparsely described with relation to DFNP (6,9,12,14,(24)(25)(26).…”
mentioning
confidence: 99%